2015
DOI: 10.5935/abc.20150035
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory and Ventilatory Power: Characterization in Patients with Coronary Artery Disease

Abstract: BackgroundCirculatory power (CP) and ventilatory power (VP) are indices that have been used for the clinical evaluation of patients with heart failure; however, no study has evaluated these indices in patients with coronary artery disease (CAD) without heart failure.ObjectiveTo characterize both indices in patients with CAD compared with healthy controls.MethodsEighty-seven men [CAD group = 42 subjects and healthy control group (CG) = 45 subjects] aged 40–65 years were included. Cardiopulmonary exercise testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
4
17
0
1
Order By: Relevance
“…Previous studies have demonstrated that peak CircP is a strong predictor of outcomes in patients with left heart failure [6,8] and adults with congenital heart disease [9], and it was also evaluated in patients with coronary artery disease [11] and in the general population [12]. Our study confirms that peak CircP can also predict prognosis in patients with IPAH, which agrees with their results.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that peak CircP is a strong predictor of outcomes in patients with left heart failure [6,8] and adults with congenital heart disease [9], and it was also evaluated in patients with coronary artery disease [11] and in the general population [12]. Our study confirms that peak CircP can also predict prognosis in patients with IPAH, which agrees with their results.…”
Section: Discussionsupporting
confidence: 91%
“…Secondary outcome: As a secondary outcome measure, the exercise capacity was assessed by CP and VP, both of which have been showed to serve as a surrogate predictor of mortality and prognosis. 16 …”
Section: Methodsmentioning
confidence: 99%
“…Recently, new variables derived from the cardiopulmonary exercise test (CPET), such as circulatory power (CP) and ventilatory power (VP) have been used for the clinical evaluation of heart failure patients as important markers of exercise limitation 16 . These indices could provide a potentially valuable measure of cardiopulmonary function in the coexistence of TM2DM and HTN.…”
Section: Introductionmentioning
confidence: 99%
“…mL O 2 /kg/min) was defined as the product of peak . VO 2 and peak SBP (24). Exercise ventilatory power (mmHg) was defined as peak SBP divided by the .…”
Section: Day 2: Maximal Exercise Testing To Determine Submaximal Loadsmentioning
confidence: 99%